PENGGUNAAN KOMBINASI BAHAN PENSTABIL DALAM PEMBUATAN VELVA KWENI (Mangifera odorata Griff.) DAN PERUBAHAN MUTU SELAMA PENYIMPANAN - Setianawati Nora Hijrah; Setiawan Budi; Yuliati Noor Lilik (Media Gizi dan Keluarga, 2002)
Velva kweni is one aflhe low fat frozen desserts, was made from kweni puree, sugar, and stabilizers and was freezed in ice cream votator to ohtain fine texture. The purpose of this researchs is to study utilization of stabilizer's combination in making velva kweni and the change of quality during storage. The organoleptic test on colour, flavour, taste, texture and melting quality showed that stabilizer's combination didn't influence preference on colour, flavour, taste, texture, and melting quality, but influenced hedonic quality of colour, flavour and texture. Stabilizer's combination influenced overrun and melting velvo kweni. Velva kweni which use CMC-Carrageenan (1:2) gave the highest overrun (25.05%). The highest melting was given velva velva kweni which use CMC-Carrageenan (1:1), that is 19 minutes 6 second. The best product was produced velva kweni which use CMC-Carrageenan (I: 1) and this velva would be stored. The results of hedonic and hedonic quality test showed that duration of storage didn 't influence preference on colour, flavour, toste, lexture and melting quality. Overrun and melling velva kweni were not Influenced duralion of storage. In contrast, duration of storage influenced decreasing water content, incerasing total soluble solid, increasing pH, decreasing total acid and decreasing vitamin C content. Overrun velva kweni during storage was 25.01-25.28%, melting 14.85-15.25 minutes, water content 76.43-77.99%, total soluble solid 14.96-19.98%, pH 3.75-3.90, total acid 0.350-0.371% and vitamin C content 17.39-23 mg/ 100g.